The Public Service Lay Out Influence of Urban Development Division in DPUTR of Bandung Regency to Employee Work Comfortness - Guruh Almunawaroh Sutisna; Inne Yuwinarsih (Jurnal Arsitektur Archicentre, 2024)
Public service in government buildings has a close connection with social interaction in each administrative area. Public service activity needs a lounge that supports staff performance in public services. As Urban Development Division in DPUTR of Bandung Regency, we have a high amount of visitors but a non-supportive performance lounge. So this case leaves a problem in spatial planning for which we need to find a solution. The purpose of this journal is to find out how much the comfort level is for humans using this building as a staff. The comfort factor will be focused on in room selection, furniture planning, and capacity levels that support staff performance. Whereas research methods using qualitative descriptive data show spatial planning in lounges will affect sirculation comfort and user activities.